-4(a+4)+8a=-2(2+4a)

Simple and best practice solution for -4(a+4)+8a=-2(2+4a) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(a+4)+8a=-2(2+4a) equation:


Simplifying
-4(a + 4) + 8a = -2(2 + 4a)

Reorder the terms:
-4(4 + a) + 8a = -2(2 + 4a)
(4 * -4 + a * -4) + 8a = -2(2 + 4a)
(-16 + -4a) + 8a = -2(2 + 4a)

Combine like terms: -4a + 8a = 4a
-16 + 4a = -2(2 + 4a)
-16 + 4a = (2 * -2 + 4a * -2)
-16 + 4a = (-4 + -8a)

Solving
-16 + 4a = -4 + -8a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '8a' to each side of the equation.
-16 + 4a + 8a = -4 + -8a + 8a

Combine like terms: 4a + 8a = 12a
-16 + 12a = -4 + -8a + 8a

Combine like terms: -8a + 8a = 0
-16 + 12a = -4 + 0
-16 + 12a = -4

Add '16' to each side of the equation.
-16 + 16 + 12a = -4 + 16

Combine like terms: -16 + 16 = 0
0 + 12a = -4 + 16
12a = -4 + 16

Combine like terms: -4 + 16 = 12
12a = 12

Divide each side by '12'.
a = 1

Simplifying
a = 1

See similar equations:

| 2=9-5w | | 1-7n-3=-2 | | 5x+y=-23 | | 6w+2w+3=9 | | -6+4(n-4)=5(2n+4) | | 7p+3-5p=-11 | | 3x-4x+1=1 | | 3x-9x+2=26 | | 3f+5=f | | 5p+2p=-4 | | 3x+8+6=50 | | 3v=75 | | -9x-4=68 | | v+3+7v=11 | | v+v=-4 | | x^2-66x+64=0 | | 6r+4r=16+2r | | 9p=2r-4f | | 2(2x-5)=2 | | 3t+3t=-9+9t | | x+1+1=6 | | 12=7+c | | -2(x-1)=-3x | | 6s+4=20+5s | | 9x^2-8x^3= | | 3(y+7)=2y-5 | | -6p+7p=0 | | 14+2y=3 | | -36-8x=7x+24 | | 6x+3x=18 | | 7+3x+5=-15 | | 2x^2-14x+2=0 |

Equations solver categories